ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KURANGNYA PENERAPAN MANAJEMEN KUALITAS (K4) PADA PERKULIAHAN DI PRODI TATA RIAS AKS-AKK - Pambudi, Ika Prasetyani (Jurnal Socia Akademika, 2024)
Quality management (K4) is an approach used to improve the quality of education in higher education, but in practice, its application in the AKS-AKK Makeup Study Program is still relatively low. The purpose of this study is to analyze the factors that influence the lack of application of quality management (K4) in lectures in the AKS-AKK Makeup Study Program. This type of research is quantitative research with an explanatory research design. The research sample was 35 people who were lecturers and education staff at the AKS-AKK Makeup Study Program who were taken using the total sampling technique. The data collection technique used a questionnaire which was then analyzed using multiple regression analysis. The results of the study showed that there was a significant positive influence, partially or simultaneously, on the factors of lecturers' understanding of quality management; infrastructure & facilities; academic culture; evaluation & monitoring on the implementation of quality management (K4) while the intitutional suport factor did not affect the implementation of quality management (K4).